2019
DOI: 10.1093/glycob/cwz055
|View full text |Cite
|
Sign up to set email alerts
|

GAG positioning on IL-1RI; A mechanism regulated by dual effect of glycosylation

Abstract: IL-1RI is the signaling receptor for the IL-1 family of cytokines that are involved in establishment of the innate and acquired immune systems. Glycosylated extracellular (EC) domain of the IL-1RI binds to agonist such as IL-1β or antagonist ligands and the accessory protein to form the functional signaling complex. Dynamics and ligand binding of the IL-1RI is influenced by presence of the glycosaminoglycans (GAGs) of the EC matrix. Here a combination of molecular dockings and molecular dynamics simulations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…11 ). The increase of the binding free energy in the glycosylated protein-ligand complexes are also reported in other studies 39 , 47 .…”
Section: Resultssupporting
confidence: 85%
“…11 ). The increase of the binding free energy in the glycosylated protein-ligand complexes are also reported in other studies 39 , 47 .…”
Section: Resultssupporting
confidence: 85%
“…The average RMSD values also show that the gmRBDfN system is the most stable. This observation was expected as several other experimental, computational, and structural studies have reported that glycosylation contributes to increasing the stability of protein structures ( Solá and Griebenow, 2009 ; Azimzadeh Irani, 2018 ; Azimzadeh Irani and Ejtehadi, 2019 ; Motamedi et al, 2021 ).…”
Section: Resultssupporting
confidence: 80%
“…We highlight case studies of cytokines with emerging diverse roles, while also showcasing experimental and theoretical approaches for understanding cytokine biochemistry. Though we cannot comprehensively discuss every avenue of investigation in this Review ( Künze et al, 2014 ; Herring et al, 2015 ; Joseph et al, 2015 ; Künze et al, 2016 ; Park et al, 2017 ; Azimzadeh Irani and Ejtehadi, 2019 ; Penk et al, 2019 ; Gangele et al, 2020 ; Roy, 2020 ; Yang, 2020 ), each of the case studies below offers a useful piece insight into an extremely complex class of biomolecules that may aid in the development of broadly applicable strategies to study molecular interactions.…”
Section: Introductionmentioning
confidence: 99%